Supporting and preparing patients for radiotherapy: Patients' and radiation therapists' perspectives on their one‐to‐one consultations. (13th July 2020) - Halkett, Georgia K.B.; Merchant, Susan; Smith, Sian K.; O'Connor, Moira; Jefford, Michael; Aranda, Sanchia; Schofield, Penelope
Abstract: Objective: Patients are often anxious and lack knowledge of radiotherapy prior to commencing treatment. Evidence‐based interventions are required to reduce patient anxiety and increase patient preparation before treatment. This study is part of a larger project examining the effectiveness of an innovative preparatory intervention "RT Prepare, " to reduce patient psychological distress prior to treatment for breast cancer. This study aimed to explore patients' and RTs' perceptions about the "RT Prepare" intervention and was conducted to assist with refinement of the intervention for future implementation. Methods: Semi‐structured interviews were conducted with patients and radiation therapists (RTs) to elicit their perspectives on the "RT Prepare" intervention. Thematic analysis was used to analyse the data. Results: Telephone interviews were conducted with 21 patients who had received the intervention and 15 RTs who had delivered the intervention. Patients and RTs described the intervention positively and highlighted that it was beneficial for preparing patients for treatment planning and treatment. The overarching themes were communication skills; preparation; information provision and dedicated space and time. Conclusion: RT Prepare was well received by patients and RTs. Practice implications Based on the results of this study and our quantitative findings, implementation of the intervention would be beneficial for both patients and RTs.